2017
DOI: 10.29252/ijrm.15.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Can letrozole plus HMG protocol improve pregnancy outcomes in frozen-thawed embryo transfer? An RCT

Abstract: Background:There are different methods in endometrial preparation for frozen-thawed embryo transfer (FET).Objective:The purpose of this study was to compare the live birth rate in the artificial FET protocol (estradiol/ progesterone with GnRH-agonist) with stimulated cycle FET protocol (letrozole plus HMG).Materials and Methods:This randomized clinical trial included 100 women (18-42 years) randomly assigned to two groups based on Bernoulli distribution. Group I received GnRH agonist [Bucerelin, 500μg subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(15 reference statements)
0
13
1
Order By: Relevance
“…To the best of our knowledge, five retrospective [2,11,12,19,20] and two clinical trial studies [9,14] have evaluated the effects of letrozole utilization for endometrial preparation before FET; however, only one of the previously published clinical trials [14] possessed a registration number in the specific clinical trial cites. The recent retrospective study, by Zhang et al in 2019 evaluated a total of 2664 patients with PCOS undergoing FET cycles, reporting that letrozole stimulation during FET cycles significantly improved live birth rates with a decrease in the pregnancy loss rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, five retrospective [2,11,12,19,20] and two clinical trial studies [9,14] have evaluated the effects of letrozole utilization for endometrial preparation before FET; however, only one of the previously published clinical trials [14] possessed a registration number in the specific clinical trial cites. The recent retrospective study, by Zhang et al in 2019 evaluated a total of 2664 patients with PCOS undergoing FET cycles, reporting that letrozole stimulation during FET cycles significantly improved live birth rates with a decrease in the pregnancy loss rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have compared the reproductive outcomes of endometrial preparation with stimulated cycles using gonadotropin and clomiphene or letrozole or both, with the artificial cycles. Notably, a number of studies have shown positive results involving ovarian stimulation (OS) for endometrial preparation in frozen embryo transfer cycles in PCOS patients [2,[8][9][10][11][12], and some studies have not found any differences compared with hormonal endometrial preparation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, HMG was added to the letrozole cycle [20]. In this study, CPR (OR 1.11, 95 % CI: 0.46-2.68) (▶ Fig.…”
Section: Letrozole Versus Acmentioning
confidence: 80%
“…The average quality of the included studies was low. Of the 10 included studies, only 1 study was an RCT (level of evidence: 2b) 20 . The other studies included 1 prospective cohort study 21 , 7 retrospective cohort studies 22 , 23 , 24 , 25 , 26 , 27 , 28 and 1 case-control study (level of evidence: 2b–4) 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation